2020
DOI: 10.1055/s-0040-1705964
|View full text |Cite
|
Sign up to set email alerts
|

Decagram Synthesis of Dimethyl 1,4-Cubanedicarboxylate Using Continuous-Flow Photochemistry

Abstract: The highly strained cubane system is of great interest as a scaffold and rigid linker in both pharmaceutical and materials chemistry. A straightforward approach is reported for the scale-up of a [2+2] photocycloaddition step using convenient home-made flow photoreactors to access dimethyl 1,4-cubanedicarboxylate on decagram-scale in 33–40% yield over 8 steps. The process is demonstrated on 3.4 g·h–1 input with 30 minutes residence time, enabling to reduce the process time and to avoid the use of batch photorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…workers 13 reported that crude 3 could only be subjected to the Favorskii rearrangement conditions after being refluxed in water to hydrolyse any methyl ketals present. As our method avoids the formation of any methyl ketals, crude 3 could undergo the desired Favorskii rearrangement without the water hydrolysis step to give crude 4.…”
Section: Entry 12)mentioning
confidence: 99%
See 3 more Smart Citations
“…workers 13 reported that crude 3 could only be subjected to the Favorskii rearrangement conditions after being refluxed in water to hydrolyse any methyl ketals present. As our method avoids the formation of any methyl ketals, crude 3 could undergo the desired Favorskii rearrangement without the water hydrolysis step to give crude 4.…”
Section: Entry 12)mentioning
confidence: 99%
“…Further optimi-zations of Tsanaktsidis's route by Linclau and co-workers allowed for the synthesis of decagram quantities of 1 in overall yields of between 33-40%. 13 Despite extensive work, current synthetic routes to 1 rely upon the synthesis of key building block dibromo-dione 2 from cyclopentanone in 5 steps (Scheme 1B). Dione 2 can then undergo an intramolecular photochemical [2 + 2] cycloaddition, which is promoted by the use of either a high-powered Hg lamp or a UV-B lamp (λ exc = 311 nm) under acidic conditions and has been successfully scaled-up using continuous flow photochemistry.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4−6 Some of its potential applications include pharmaceuticals (a rigid cubane cage is considered a phenyl bioisoster), 7−9 fuels, 6 explosives, 10,11 building blocks in material chemistry, 12,13 etc. The recently published decagram synthesis 14 of one of the key building blocks, dimethyl cubane-1,4-dicarboxylate, in combination with the rapid development of new chemical tools allowing the functionalization of its scaffold 15,16 clearly indicates that the synthesis of cubane derivatives has not reached its end yet.…”
Section: ■ Introductionmentioning
confidence: 99%